Rab11 is required for lysosome exocytosis through the interaction with Rab3a, Sec15 and GRAB - Escrevente, Cristina (2021)
Funding: This study was supported by Fundaçã o para a Ciência e Tecnologia (FCT): C.E. was supported by a post-doctoral fellowship (SFRH/BPD/78491/2011), L.B.-L. by a PhD fellowship (SFRH/BD/131938/2017) and D.C.B. by the FCT Investigator Program (IF/00501/2014/CP1252/CT0001). This work was developed with the support from the research infrastructure PPBI-POCI-01-0145-FEDER-022122, co-financed by FCT (Portugal) and Lisboa2020, under the PORTUGAL2020 agreement (European Regional Development Fund). This article was supported by the LYSOCIL project. This project has received funding from the European Union’s Horizon 2020 research and innovation programme under grant agreement No. 811087. Deposited in PMC for immediate release.